AI and the Future of Higher Education - Aroonmanakun, Wirote (Journal of New Horizon in Higher Education, 2023)
The integration of Artificial Intelligence (AI) in higher education has the potential to bring many benefits, such as personalization, automation of certain tasks, and improvement of student outcomes. However, the implementation of AI in higher education also poses a number of limitations and challenges, such as lack of transparency, bias, job displacement, lack of creativity, privacy and security, and lack of human interaction. Additionally, it is important to consider the ethical considerations and implications of AI integration in higher education. This paper explores the current state of AI integration in higher education, the potential benefits, limitations and challenges of AI integration in higher education, and the ethical considerations that must be taken into account when implementing AI systems in higher education. The paper also highlights the importance of responsible and ethical implementation of AI in higher education, ongoing evaluation and monitoring of the impact of AI on student outcomes and experiences, and the potential long-term implications of AI integration in higher education.